Exposure of human fallopian tube epithelium to elevated testosterone results in alteration of cilia gene expression and beating. Issue 9 (5th August 2020) - Jackson-Bey, Tia; Colina, José; Isenberg, Brett C; Coppeta, Jonathan; Urbanek, Margrit; Kim, J Julie; Woodruff, Teresa K; Burdette, Joanna E; Russo, Angela
Abstract: STUDY QUESTION: How does exposure to a testosterone rich environment affect the function and gene expression of human fallopian tube epithelium (hFTE)? SUMMARY ANSWER: Elevated testosterone level alters several gene transcripts that regulate cilia expression and negatively impacts the rate of cilia beating. WHAT IS KNOWN ALREADY: The presence of estrogen in the follicular phase of the menstrual cycle increases the human fallopian tube ciliary beating frequency. The luteal phase, triggered by ovulation and increasing progesterone, is marked by a decrease in ciliary beating. Women with polycystic ovarian syndrome (PCOS) may have twice the serum level of testosterone than ovulatory women. To date, the effect of elevated androgens on the function of the human fallopian tube is not well-understood. We chose to examine the impact of elevated testosterone on hFTE. STUDY DESIGN, SIZE, DURATION: A prospective basic science study of human fallopian tube specimens from reproductive-aged women undergoing benign gynecologic surgery was performed. Fallopian tube removal at a large US academic center was collected and provided to us to continue with epithelium isolation and culturing. A total of 12 patients were analyzed in the study. PARTICIPANTS/MATERIALS, SETTING, METHODS: Fallopian tube epithelium was isolated and exposed to two different conditions: normal with low testosterone concentration of 0.8 nM and PCOS-like, with high testosterone concentration of 2 nM. The study was conducted in both static and dynamic conditions in microfluidic devices for a total of 14 days, after which the tissue was collected for processing including RNA extraction, quantitative PCR and immunohistochemistry. After the first 7 days of each experiment, a sample of tissue from each condition was imaged to quantify cilia beating frequency. MAIN RESULTS AND THE ROLE OF CHANCE: hFTE exposed to the 2 nM testosterone displayed slower cilia beating, inhibited estrogen signaling and decreased expression of the ciliary marker FOXJ1 when compared to stimulation with 0.8 nM testosterone. LARGE SCALE DATA: N/A. LIMITATIONS, REASONS FOR CAUTION: The in vivo response to elevated testosterone may differ from in vitro studies. RNA amount was limited from tissue cultured in the microfluidic devices as compared to static culture. WIDER IMPLICATIONS OF THE FINDINGS: Understanding elevated testosterone in tubal function may explain an additional contribution to subfertility in women with PCOS and other hyper-androgen disorders, aside from oligo-ovulation. Furthermore, this adds to the body of literature of fallopian tube function using a microfluidic device. STUDY FUNDING/COMPETING INTEREST(S): NIH grants: UH3 ES029073 and R01 CA240301. There are no competing interests.